Clickable Poly(ionic liquids): A Materials Platform for Transfection. Issue 40 (31st August 2016) - Freyer, Jessica L.; Brucks, Spencer D.; Gobieski, Graham S.; Russell, Sebastian T.; Yozwiak, Carrie E.; Sun, Mengzhen; Chen, Zhixing; Jiang, Yivan; Bandar, Jeffrey S.; Stockwell, Brent R.; Lambert, Tristan H.; Campos, Luis M.
Abstract: The potential applications of cationic poly(ionic liquids) range from medicine to energy storage, and the development of efficient synthetic strategies to target innovative cationic building blocks is an important goal. A post‐polymerization click reaction is reported that provides facile access to trisaminocyclopropenium (TAC) ion‐functionalized macromolecules of various architectures, which are the first class of polyelectrolytes that bear a formal charge on carbon. Quantitative conversions of polymers comprising pendant or main‐chain secondary amines were observed for an array of TAC derivatives in three hours using near equimolar quantities of cyclopropenium chlorides. The resulting TAC polymers are biocompatible and efficient transfection agents. This robust, efficient, and orthogonal click reaction of an ionic liquid, which we term ClickabIL, allows straightforward screening of polymeric TAC derivatives. This platform provides a modular route to synthesize and study various properties of novel TAC‐based polymers. Abstract : They just clicked : A stable bis(dialkylamino)cyclopropenium chloride salt can efficiently react with polymers containing secondary amines to yield cationic polyelectrolytes. The dialkylamino groups in this click transformation can be modulated to yield various polyelectrolytes bearing soft cationic moieties. Some of these cyclopropenium‐based polymers give high transfection efficiencies and are less cytotoxic than linear polyethyleneimine (PEI).